Análisis del impacto del síndrome de burnout en el rendimiento laboral de los servidores públicos del GAD Municipal del cantón Portoviejo - Andrade Napa, Gema Lisbeth (2025)
This research aimed to analyze burnout syndrome and its relationship with job performance among public servants of the Municipal Decentralized Autonomous Government (GAD) of Portoviejo canton. The methodology used was descriptive in nature, including bibliographic and field research, as well as inductive, deductive, and analytical-synthetic methods. Both qualitative and quantitative techniques were applied: a structured interview with the Human Resources manager of the Municipal GAD of Portoviejo and a survey of public servants from various departments. The tools used included the Maslach Burnout Inventory (MBI) to measure three dimensions of burnout (emotional exhaustion, depersonalization, and personal accomplishment), the Likert scale, and Google Forms as a digital, efficient, and secure data collection medium. It was concluded that 38.20% of public servants experience high levels of emotional exhaustion and 39.33% a moderate level. Internal document review revealed deficiencies in existing policies and procedures to prevent burnout, highlighting that they are limited and lack a structured approach to comprehensively address contributing factors to the syndrome. Emotional exhaustion manifested in signs of fatigue, decreased productivity, and impacts on overall well-being. Moreover, the importance of implementing an improvement plan was identified—one that includes periodic assessments, awareness and support strategies focused on the prevention and management of burnout. In conclusion, this approach will help strengthen employee well-being and improve their job performance, ultimately enhancing the quality of services provided by the GAD.